2001
DOI: 10.1007/s002210100722
|View full text |Cite
|
Sign up to set email alerts
|

The effect on corticospinal volleys of reversing the direction of current induced in the motor cortex by transcranial magnetic stimulation

Abstract: Descending corticospinal volleys were recorded from a bipolar electrode inserted into the cervical epidural space of four conscious human subjects after monophasic transcranial magnetic stimulation over the motor cortex with a figure-of-eight coil. We examined the effect of reversing the direction of the induced current in the brain from the usual posterior-anterior (PA) direction to an anterior-posterior (AP) direction. The volleys were compared with D waves evoked by anodal electrical stimulation (two subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
207
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 222 publications
(228 citation statements)
references
References 6 publications
17
207
2
2
Order By: Relevance
“…This experiment was performed in subject 6. As reported previously (Di Lazzaro et al 2001;Sakai et al 1997), a single AP test pulse recruited a small D wave and an I3 wave. In addition, there was a small I4 wave that had a slightly longer latency (0.3 ms) than that seen after PA stimulation and a very small wave in the latency range of the I5 wave (Fig.…”
Section: Control Experimentssupporting
confidence: 75%
“…This experiment was performed in subject 6. As reported previously (Di Lazzaro et al 2001;Sakai et al 1997), a single AP test pulse recruited a small D wave and an I3 wave. In addition, there was a small I4 wave that had a slightly longer latency (0.3 ms) than that seen after PA stimulation and a very small wave in the latency range of the I5 wave (Fig.…”
Section: Control Experimentssupporting
confidence: 75%
“…Several studies have discussed this issue. Although a number of studies have shown that MEP amplitude was altered by the use of various current directions (Di Lazzaro et al 2001;Sakai et al 1997;Werhahn et al 1994), Chen et al (2003) and Ni et al (2009) showed that the current direction of the CS did not affect the degree of IHI. If the contralateral corticospinal output affects the degree of IHI, different degrees of IHI would be detected during the use of various CS current directions.…”
Section: Discussionmentioning
confidence: 99%
“…We do not know the reason for the broad distribution of optimal orientation for the lowest stimulus thresholds in our participants. Changing the direction of the induced current affects the shape of the motor evoked potential (Di Lazzaro et al, 2001;Dubach et al, 2004;Takahashi et al, 2005;Trompetto et al, 1999) and the duration of the cortical silent period (Orth and Rothwell, 2004) as if different neural structures or circuits respond optimally at different orientations of the coil. Variations in the microscopic anatomy across subjects may explain this variability of the optimal coil orientation.…”
Section: Discussionmentioning
confidence: 99%